Relative-price changes and demand factors in the period of quantitative easing in Japan - Bernd Hayo; Hiroyuki Ono (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
Concentrating on the period of quantitative easing in Japan, this paper reexamines the correlation between the asymmetry of sectoral relative-price changes and the aggregate inflation rate. This correlation is widely interpreted as evidence that short-run inflation is determined by supply-side factors; however, we study whether, in addition to the inflation rate, monetary environment and aggregate demand explain this correlation. Using producer price index data, we show, first, that the positive and significant effect of relative-price change asymmetries on inflation is not robust with respect to various indicators of asymmetry. Second, indicators of aggregate demand and monetary environment affect the measures of asymmetries, which raises doubt about whether they can be interpreted as pure supply-side indicators. Third, in addition to the indirect effect via measures of asymmetries, demand and monetary factors directly affect inflation. Thus, we reject the claim that the recent disinflation/deflation period can be understood as primarily a supply-side phenomenon.
Keywords: E20; E31; E52; E65; O53; 330; Japan; supply side; inflation; deflation; price-change asymmetries; quantitative easing; Geldpolitik; Inflation; Relativer Preis; Gesamtwirtschaftliche Nachfrage; Japan